A new green approach to L-histidine and β-alanine analysis in dietary supplements using rapid and simple contactless conductivity detection integrated with high-resolution glass-microchip electrophoresis - Pukleš, Iva; Páger, Csilla; Sakač, Nikola; Matasović, Brunislav; Kovač-Andrić, Elvira; Šarkanj, Bojan; Samardžić, Mirela; Budetić, Mateja; Molnárová, Katarína; Marković, Dean; Vesinger, Ana; Jozanović, Marija (Analytical and bioanalytical chemistry, 2024)
The analysis of dietary supplements is far less regulated than pharmaceuticals, leading to potential quality issues. Considering their positive effect, many athletes consume supplements containing L-histidine and β-alanine. A new microfluidic method for the determination of L-histidine and β-alanine in dietary supplement formulations has been developed. For the first time, capacitively coupled contactless conductivity detection was employed for the microchip electrophoresis of amino acids in real samples. A linear relationship between detector response and concentration was observed in the range of 10-100 µmol L-1 for L-histidine (R2 = 0.9968) and β-alanine (R2 = 0.9954), while achieved limits of detection (3 × S/N ratio) were 4.2 µmol L-1 and 5.2 µmol L-1, respectively. The accuracy of the method was confirmed using recovery experiments as well as CE-UV-VIS and HPLC-UV-VIS techniques. The developed method allows unambiguous identification of amino acids in native form without chemical derivatization and with the possibility of simultaneous analysis of amino acids with metal cations.
Keywords: Amino acids; Glass; sklo; potravní doplňky; elektrická vodivost; Limit of Detection; limita detekce; Microchip electrophoresis; Electrophoresis, Microchip; Green Chemistry Technology; l-Histidine; β-Alanine; Electric Conductivity; histidin; Dietary Supplements; beta-alanin; Capacitively coupled contactless conductivity detection; beta-Alanine; elektroforéza mikročipová; Histidine; Dietary supplements; technologie zelené chemie